Spectrophotometric Characterization of lycopene Phytosomes from Fruit Peels of Lycopersicum esculentum - Viresh K Chandur; Ramakrishna Shabaraya A (Indian Journal of Pharmacy & Drug Studies, 2023)
Among all colored fruits tomatoes are one of the rich source of lycopene, which is essentially known for its anti-oxidant activity and effective in treating major diseases like cancer, heart diseases. It is insoluble in water and sensitive to light and temperature but, it is soluble with various proportions in aprotic solvents like petroleum ether, diethyl ether, and acetone. Best combination of these solvents was made used to extract lycopene and characterized for its standardization by means of phytochemical testing, melting point, λ max, FTIR and DSC studies showing the effective way of extraction with good yield up to 8%, phytochemical investigation showed presence of flavonoids, turpinoids and steroids. UV Spectrophotometric analysis shows λ max at 471nm. FTIR studies show the presence of conjugated carbon double bonds essential to get red color to the product and open ring structure on both the ends. DSC endotherms, the melting peak obtained for the phytosomal complex was less than the melting point obtained for the lycopene and is due to the less cohesive force energy of crystal lattice of the complex.